Effects of Emotional Intelligence and Locus of Control on the Psychological Well-Being of Adolescents with Visual Impairment (2011)
Psychological well-being of adolescents with visual impairment has been a source of great concern. Most often, efforts have been focused on academic progress, achievements and performance, with very little attention given to their psychological well-being. The attainment of a good quality psychological well-being of adolescents with visual impairment is observed to be fundamental in order to cope with the challenges imposed on them by their visual impairment. Observably, the documented training programmes on Emotional intelligence and Locus of Control focused on adolescents without visual impairment. This study, on the contrary investigated the effectiveness of emotional intelligence and locus of control training in enhancing the psychological well-being of adolescents with visual impairment in Oyo and Ondo States, Nigeria. A Pretest-posttest, control group, quasi experimental design with 3x2x2 factorial matrix was adopted. The sample consisted of one hundred and twenty participants with visual impairment. Ninety-one totally blind and twenty-nine partially sighted adolescents were drawn from three integrated secondary schools purposively selected for the study; junior secondary school classes I and II and senior secondary school classes I and II. They were randomized into the two treatment conditions (Emotional Intelligence and Locus of Control) and the control group. Two instruments – Snellen Scale (Screening Scale) and the adapted version of Ryff’s Scale of Psychological Well-being (r=0.77) were used. Seven null hypotheses were tested at 0.05 level of significance, data were analysed using Analysis of Covariance (ANCOVA) and Duncan post hoc test. There was significant main effect of treatment on the psychological well-being of the participants (F(2,107) = 21.02; p<0.05). The Emotional Intelligence group had the highest post-test psychological well-being mean score (x= 80.0), followed by the Locus of Control group (x=75.1) and then the control group ( x = 61.5). Type of visual impairment had no main significant effect on the participants’ psychological well-being though the partially sighted obtained higher post-test psychological well-being score ( x = 74.9) than those with total blindness ( x =71.1). Gender had no significant main effect on psychological well-being of adolescents with visual impairment. Male participants recorded higher mean score ( x = 72.1) while female participants had mean score ( x = 70.1). Also no significant interaction effects of treatment, gender and type of visual impairment on the psychological well-being of participants were observed.Emotional intelligence and Locus of control training were effective in enhancing the psychological well-being of adolescents with visual impairment. Therefore, the two treatments were recommended for use in managing adolescents with visual impairment. It is recommended that adolescents with total blindness should be exposed to more therapeutic treatments in order to improve on other areas of psychological problems